2017
DOI: 10.18006/2017.5(1).098.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different pre-treatments and germination media on seed germination and seedling growth of Parkia timoriana (DC.) Merr

Abstract: Parkia timoriana (DC.) Merr. is one of the lesser known multipurpose leguminous tree species found in North East India. Like many other legumes this species too have hard coated seeds which prevent seed germination and thus there is a need to investigate the most appropriate method to break its dormancy. Six pre treatments (tap water, gibberellic acid (GA3) @ 500 ppm, stratification, sulphuric acid @ 98%, boiling water and nicking) and two media (top of paper (TOP) and sand) were use to evaluate seed germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
2
0
6
Order By: Relevance
“…This finding was related to the lack of immersion in water for the seeds in the ES treatment. In contrast, the results showed that immersion in water after scarification increases the moisture content in the seeds and enables the activation of metabolic processes and embryonic development (Tambelini & Perez, 1998;Thangjam & Sahoo, 2017) and that even in freshly collected seeds, the higher the concentration of hydrophobic substances is, the more difficult the germination is. Treatments with mechanical scarification and immersion in water were more efficient for overcoming dormancy compared with the treatments that only used scarification, regardless of storage time ( Figure 3A; Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…This finding was related to the lack of immersion in water for the seeds in the ES treatment. In contrast, the results showed that immersion in water after scarification increases the moisture content in the seeds and enables the activation of metabolic processes and embryonic development (Tambelini & Perez, 1998;Thangjam & Sahoo, 2017) and that even in freshly collected seeds, the higher the concentration of hydrophobic substances is, the more difficult the germination is. Treatments with mechanical scarification and immersion in water were more efficient for overcoming dormancy compared with the treatments that only used scarification, regardless of storage time ( Figure 3A; Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…Prior to germination, the seeds were soaked and manually scarified by secateurs and cutting the seed coat approximately 1 mm from the opposite side of helium [12]. Scarified seeds were rinsed and steeped in distilled water (1:10 w/v) for 24 h, washed, and placed in a damp cotton towel.…”
Section: Germinated Nitta Bean (Nbg)mentioning
confidence: 99%
“…До головних біологічних функцій гіберелінів належать регуляція процесів проростання насіння, координація поділу клітин і їхнього розтягу, детермінування статі, розвиток пилку і квіток, індукція цвітіння, формування насіння та плодів (Gantait et al, 2015;Kosakivska et al, 2019). Екзогенну обробку гіберелінами успішно використовують для покращення ростових характеристик сіянців різних деревних видів (Ameen, Al-Imam, 2007;Elo et al, 2009;Maku et al 2014;Acar et al, 2017;Thangjam, Sahoo, 2017;Yuan al., 2019;Yücedağ et al, 2019).…”
Section: висновкиunclassified
“…Merr. (Thangjam, Sahoo, 2017), проростання насіння та ріст сходів рослин Mansonia altissima (Maku et al, 2014).…”
Section: біометрична характеристика проростків і сіянцівunclassified
See 1 more Smart Citation